1994
DOI: 10.1111/j.1532-5415.1994.tb06593.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Related Factors Among Nursing Home Residents

Abstract: The results suggest that living conditions and factors related to health and functional capacity affect the level of physical activity among nursing home residents. In order to encourage this population to be physically active, attention should be paid not only to physical exercise but also to associated factors, such as satisfaction with everyday life and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 15 publications
5
45
0
1
Order By: Relevance
“…This review indicates that barriers operate at multiple levels. Thus, socioecological frameworks, which emphasize the importance of examining factors and their interconnections at multiple levels of a system (e.g., individual, organizational, policy; Richard et al, 1996;Sallis et al, 2006) would be useful to guide future research on how barriers intersect and how they can be addressed through multiple-intervention programs. The consistent use of a typology of resident, organizational, environmental, and other barriers to the promotion of physical activity in LTC would help to inform the development of costeffective and sustainable approaches to physical activity enhancement in these settings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This review indicates that barriers operate at multiple levels. Thus, socioecological frameworks, which emphasize the importance of examining factors and their interconnections at multiple levels of a system (e.g., individual, organizational, policy; Richard et al, 1996;Sallis et al, 2006) would be useful to guide future research on how barriers intersect and how they can be addressed through multiple-intervention programs. The consistent use of a typology of resident, organizational, environmental, and other barriers to the promotion of physical activity in LTC would help to inform the development of costeffective and sustainable approaches to physical activity enhancement in these settings.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of examining factors and their interconnections across system levels when using socioecological models has been stressed by a number of authors Richard et al, 1996;Sallis & Owen, 1997;Sallis et al, 2006). Most of the literature reviewed lacked a description of barriers at multiple levels, suggesting the absence of an underlying socioecological model to guide variable selection.…”
Section: Use Of a Socioecological Model And A Multiple-intervention Amentioning
confidence: 99%
See 2 more Smart Citations
“…A nursing home can refl ect a passive environment; in one study, more than 30 % of the residents reported a decrease in physical activity during their stay in a nursing home, despite their largely positive attitude towards physical exercise (Ruuskanen and Parkatti , 1994 ). As a result, ambulatory residents sit down for long periods (MacRae et al , 1996 ) and they spend daily only 137 min upright, including 94 min standing and 43 min walking (Egerton and Brauer , 2009 ).…”
Section: Physical Inactivitymentioning
confidence: 99%